Taxonomía de los hongos: un rompecabezas al que le faltan muchas piezas (2023)
ABSTRACT: Fungi are multifaceted organisms found in almost all ecosystems on Earth, where they establish various types of symbiosis with other living beings. Despite being recognized by humans since ancient times, and the high number of works delving into their biology and ecology, much is still unknown about these organisms. Some criteria classically used for their study are nowadays limited, generating confusion in categorizing them, and even more, when trying to understand their genealogical relationships. To identify species within Fungi, phenotypic characters to date are not sufficient, and to construct a broad phylogeny or a phylogeny of a particular group, there are still gaps affecting the generated trees, making them unstable and easily debated. For health professionals, fungal identification at lower levels such as genus and species, is enough to select the most appropriate therapy for their control, understand the epidemiology of clinical pictures associated, and recognize outbreaks and antimicrobial resistance. However, the taxonomic location within the kingdom, information with apparently little relevance, can allow phylogenetic relationships to be established between fungal taxa, facilitating the understanding of their biology, distribution in nature, and pathogenic potential evolution. Advances in molecular biology and computer science techniques from the last 30 years have led to crucial changes aiming to establish the criteria to define a fungal species, allowing us to reach a kind of stable phylogenetic construction. However, there is still a long way to go, and it requires the joint work of the scientific community at a global level and support for basic research.